The historical-axiological context of the relationship democracy - Church: George Weigel's Position - Jasiński, Karol (Studia Warmińskie, 2019)
The author of the paper focused on the analysis of the relationship between a democratic state and the Church. The point of reference are the views of the American intellectual George Weigel. The paper has two parts. The first one draws attention to the sources (its Christian roots) and contemporary problems of the democratic system in Europe (postulate of moral revolution in the face of a crisis manifested in wrong humanity, Christophobia, disappearance of the spiritual dimension, historical amnesia, proceduralism and exclusive humanism). In the second one, the desirable place and role of the Church in the contemporary democratic state is shown (separation of the Church from state institutions and direct political activity, preservation of one's own identity, shaping the morality of man and society, active participation in creating a civil society).